Innovation Strategy and SME Survival: The Role of Organizational Adaptability - Karikari Amoa-Gyarteng; Oyin-Emi Eserifa (Horizons of Innovation: Conference on Multidisciplinary Trends in Science 2024, 2024)
This study aims to concisely examine the impact of innovation strategy on the survival of small and medium enterprises (SMEs), focusing on the mediating role of organizational adaptability. Employing an explanatory research design, data were collected through structured questionnaires from SME owners and managers in Kumasi Metro, Ghana. Regression analysis reveals that innovation strategy is significantly related to organizational adaptability, which in turn positively influences SME survival. Therefore, organizational adaptability's mediating role is established, indicating its essential function in SME survival.
Keywords: 650; Innovation strategy; organizational adaptability; SME survival; diffusion of innovation theory; competitive advantage